SYSTEM MEMORY CACHE ON MICROPROCESSORS - Datwi Wahyudi; Jalinas, SKom, MM Jalinas, SKom, MM (Jurnal Sistem Komputer, 1997)
In this writing assignment is discussed about the system cache memory on the microcomputer system with memoi cache on the microprocessor that is useful to speed up computer performance. type of cache used is of type M-way set-associative caches on microprocessors is a Two-way associative cache. Suitable for this type of cache operations multiprosesing because relatively inexpensive and simple. Microprocessor has a separate cache memory data cache, for data and code for instruction cache.  The cache memory itself is a technique to improve overall system performance by combining a small random access memory with a large conventional RAM (which is slower but cheaper), so that would be obtained by high-speed memory that a large capacity with relatively cheap price.